Interview of Richard E. Byrd by Martha Deane, October 26, 1953 - Byrd, Richard Evelyn, 1888-1957 (Byrd Polar Research Center Archival Program, 1953)
The media can be accessed here: http://streaming.osu.edu/knowledgebank/byrd/8908.mp3 Martha Deane interviews Byrd, his opinion on socialism, power of government, communism and human relations. Additionally Byrd talks about his stay in Antarctica and how he almost died of carbon monoxide poisoning from the stove in his shack during his second expedition to Antarctica (1933-1935). Digital preservation funded by the Kane Lodge Foundation, Inc., New York, New York.